Stress vulnerability in male youth with Internet Gaming Disorder. (March 2017) - Kaess, Michael; Parzer, Peter; Mehl, Laura; Weil, Luisa; Strittmatter, Esther; Resch, Franz; Koenig, Julian
Highlights: Vulnerability to stress is a potential predisposing factor for Internet Gaming Disorder [IGD]. Neurobiological studies addressing mechanisms of stress vulnerability in IGD are missing. 24 young men with IGD and 25 matched controls completed the Trier Social Stress Test. IGD patients showed an attenuated cortisol response and greater negative affect in response to acute stress. Alterations of the stress response systems may be involved in the development and maintenance of IGD. Abstract: Internet Gaming Disorder [IGD] was introduced as new behavioral addiction in DSM-5 Section 3. Vulnerability to stress is a potential predisposing factor for IGD. Given a lack of preexisting empirical data, the study investigated differences in the psychological and neurobiological response to acute stress in patients with IGD. 24 young men (mean age 18.38 years; range 13–25 years) fulfilling DSM-5 criteria for IGD and 25 matched controls underwent the Trier Social Stress Test [TSST]. Participants provided hair samples for the analysis of basal hypothalamic-pituitary-adrenal [HPA] axis activity and clinical interviews were conducted to assess psychopathology. During the experiment, participants reported on their subjective stress experience and momentary affect, provided samples of salivary cortisol and their heart rate was continuously recorded. Patients with IGD reported greater everyday and chronic stress, as well as psychopathological comorbidity. No differences were found on measures of hair cortisol. Compared to controls, IGD patients showed an attenuated cortisol response (χ 2 (7) = 25.75, p < 0.001 ) and greater negative affect (χ 2 (7) = 17.25, p = 0.016 ) in response to acute stress. Heart rate (χ 2 (1) = 5.49, p = 0.019 ), negative affect (χ 2 (1) = 5.60, p = 0.018 ) and subjective stress (χ 2 (1) = 5.55, p = 0.019 ) were transiently increased in IGD patients. After adjusting for sportive activities, IGD patients showed transiently decreased cortisol (χ 2 (1) = 5.20, p = 0.022 ), potentially indicating general HPA-axis dysfunction beyond altered reactivity. Stress reactivity showed correlations with IGD symptom severity. Findings illustrate differences in acute psychological and neurobiological stress reactivity in patients with IGD. Alterations of the stress response system may be involved in the development and maintenance of IGD.